(untitled) (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we investigate the cycles and fixed point sets of compositions of resolvents using Attouch–Thera duality. We demonstrate that the cycles defined by the resolvent operators can be formulated in Hilbert space as solutions to a fixed point equation. Furthermore, we introduce the relationship between these cycles and the fixed point sets of the compositions of resolvents.